Households, agroecosystems and rural resource management - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1992)
Households, agroecosystems and rural resources management by Clive Lightfoot, Shelley Feldman and M Zainul Abedin 1991 80pp, ISSN 0116 5720 ISBN 971 1022 89 3 Pbk The Bangladesh Agricultural Research Institute, Joydebpur BANGLADESH